Effects of Cigarette Smoke on Tissue Trace Element Concentration of Rats Exposed to Second-hand Smoke - Kivanc Ergen (Medicine Science, 2012)
Trace elements have an important effect on and play a key role in a variety of the processes necessary for life. Studies have indicated a definite correlation between content of trace elements and many common diseases. It has been concluded that smoking may be a substantial source of intake of these hazardous elements, not only to the smoker, but to nonsmokers via passive smoke, as well. Even passive intake of such elements can change the metabolism of other trace elements and influence their concentrations. In order to assess their potential role in some human diseases, it is necessary to measure trace element concentrations in various tissues in experimental models. In this study, liver, kidney and spleen tissue samples from rats exposed to secondhand smoke were analysed for Fe, Cu, Zn, Cr, Mn and Co trace element levels by atomic absorption spectrophotometer. Cr, Mn, Fe and Co levels in the liver, Fe and Co levels in the kidney, and Zn, Cu, Mn and Co levels in the spleen were significantly lower than those of controls, but Cu levels in the kidney and Fe levels in the spleen were significantly higher than those of controls. Our data suggest that chronic exposure to cigarette smoke alters the trace element concentration of various tissues in rats exposed to secondhand smoke. These alterations may be attributable to oxidative stress produced by cumulative effect of inhaled smoke rather than the toxic effect of absorbed toxic metals. Low Mn levels in the liver and spleen, increased Cu levels in kidney and Fe levels in the spleen, and changes in the metabolism of Zn, Fe and Cu may be indicators of oxidative stress. Decreases in Co and Cr levels in rats exposed to secondhand smoke may also be related to the intake of the toxic trace elements present in cigarette smoke. [Med-Science 2012; 1(1.000): 1-12]